Gestational age assessment of neonates using foot and hand length measurements: a cross sectional tertiary care centre study - Sajjan, Shruti M.; Malik, Sushma; Lichade, Vinaya M.; Wade, Poonam (International Journal of Research in Medical Sciences, 2022)
Background: Gestational age of neonates computed based on Naegele’s formula, ultrasound, or using modified New Ballard score (NBS) is limited in the community setup due to illiteracy, accessibility and expertise. Hence there should be alternative technique which can be done even by inexperienced health care staff and in rural communities. Objective of current study was to find out the correlation of foot and hand length with gestational age among neonates. Methods: A cross sectional study including 200 neonates and their foot length, hand length, birth weight was recorded. Gestational age assessment was done using modified NBS. Correlation among various study parameters was done using Pearson’s correlation coefficient. Results: Of the 200 neonates studied, the mean foot length was 7.1±0.46 cm with a range of 4-8.5 cm. The mean hand length was 6.0±0.71 cm with a range of 3.8-7.4 cm. The mean foot and hand length of term neonates was higher than preterm neonates. The mean foot and hand length of normal weight neonates was higher than Low birth weight neonates. Conclusions: Foot and hand length is a simple, quick and reliable measurement which can be used as a proxy measurement to gestational age assessment. It can be easily measured by traditional birth attendants in the community.